Brand relationships and risk: influence of risk avoidance and gender on brand consumption - Seung-Hee Lee; Jane E. Workman; Kwangho Jung (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
Recent brand relationship research has paid attention to brand love, brand credibility, and brand loyalty. In market and society, various collaborations and co-creations derived from brand relationships generate various social network markets and open business innovations. Brand relationships and collaborative forms heavily depend on risk taking or risk avoidance. However, few studies have examined how brand relationship is related to risk avoidance. The purpose of this study is to investigate the influence of risk avoidance and gender on brand trust, brand credibility, brand loyalty, and brand choice overload. We review relevant literature on brand relationship and risk avoidance and develop research hypotheses about brand relationship and risk. We find that consumers' risk avoidance influences brand trust, brand credibility, brand loyalty, and brand choice overload. We suggest implications about how brand relationships can promote social network markets and open business innovations through social construction process.
Keywords: 650; Brand relationship; Brand trust; Brand credibility; Brand choice overload; Risk avoidance; Social network markets